Aggregated Science: An Examination of Three Multi-Disciplinary Databases. - J. B. Hill (Issues in Science and Technology Librarianship)
Multi-disciplinary aggregator databases index, abstract, and aggregate full-text electronic content from a wide variety of publishers on a wide variety of subjects. This study examines the scientific content of three leading aggregator databases: Bell & Howell's Research Library (Core and Sciences modules), Ebsco's Academic Search Elite, and Gale's Expanded Academic ASAP. While these databases are similar in scope, a detailed analysis of titles indicates that each database has relative strengths and weaknesses and that each database has a significant amount of unique full-text content.